Pengembangan Latihan Ketepatan Tendangan dalam Sepakbola untuk Anak Kelommpok Umur 13-14 Tahun - Anam, Khoiril (Universitas Negeri Semarang, 2013)
This study aims to produce a model of practice kick accuracy in football for the age group of 13 to 14 years old children feasible to use. The study used research and development design, consisting the steps of (1) identified the potential and problems, (2) collect data, (3) develop initial products, (4) design a validation, (5) design revision, (6) small-scale product test, 7)product revision, (8) large-scale test, (9) product revision, and (10) the final result. Product quality assessment involving 3 experts. Instruments used for data collection are general guideline interviews, field notes, questionnaire validation value scale, the observation model, the effectiveness of observation model, and a questionnaire for students. The quantitative descriptive analysis and the qualitative descriptive analysis techniques are used to collect the data. The result of this research is a model of practice kick accuracy consisting of (1) triangular passing game; (2) passing and moving game; (3) moving the ball game; (4) passing the ball game; (5) passing and coordination game; (6) scoring goal game; (7) target ball game of 4 vs 2 ; (8) target goal game of 2 vs 1; and (9) target goal game of 2 vs 2, arranged in a training DVD shape and training handbook.